CMB Temperature Polarization Correlation and Primordial Gravitational Waves: WMAP5 - N. J. Miller; B. G. Keating; A. G. Polnarev (Advances in Astronomy)
we continue our study of the CMB temperature polarization (TE) cross-correlation as a source of information about primordial gravitational waves (PGWs). In a previous paper, we considered two methods for detecting PGWs using the TE cross-correlation. The first method is the zero multipole method, where we find the multipole, ℓ0, where the TE cross-correlation power spectrum, CℓTE, first changes sign. The second method Wiener filters the CMB TE data to remove the density perturbation contribution to the TE power spectrum. We then use statistical tests to determine if there is a detection of negative residual TE correlation and hence a detection of primordial gravitational waves, the only source of negative TE correlation at these superhorizon scales. In this paper, we will apply these tests to the WMAP 5-year data. We find that the TE power spectrum consistent with r < 2.0 at 95% confidence with no additional assumptions about the PGWs. If we assume that the PGWs are generated by inflation, then we get r < 1.0 at 95% confidence.